The ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA TIPE PISA PADA MATERI CHANGE AND RELATIONSHIP - Fauzan Zulfendri, Ahmad; Yuhana, Yuyu; Hendraya, Aan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This descriptive qualitative research aimed to analyze the errors made by 11th-grade students (25 students) in solving 6 PISA-type word problems on the topic of "Change and Relationship" based on Newman's Error Analysis (NEA) stages. The results demonstrated the distribution of errors as follows: (1) Reading Error at 0% (0 students); (2) Comprehension Error at 10.57% (13 errors); (3) Transformation Error at 18.70% (23 errors); (4) Process Skills Error at 21.95% (27 errors); and (5) Encoding Error at 48.78% (60 errors). Factors causing these errors included low dynamic algebraic reasoning, a tendency to memorize procedural formulas mechanically, and students' unfamiliarity with the characteristics of non-routine PISA-type word problems.